2009
DOI: 10.1016/j.bbagen.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of integrin activity and signalling

Abstract: The ability of cells to attach to each other and to the extracellular matrix is of pivotal significance for the formation of functional organs and for the distribution of cells in the body. Several molecular families of proteins are involved in adhesion, and recent work has substantially improved our understanding of their structures and functions. Also, these molecules are now being targeted in the fight against disease. However, less is known about how their activity is regulated. It is apparent that among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
179
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 198 publications
(189 citation statements)
references
References 163 publications
(196 reference statements)
3
179
0
7
Order By: Relevance
“…However, integrin function is regulated by changes in phosphorylation and protein interactions in the cytoplasmic domains. [7][8][9][10] LFA-1 and a 4 b 1 mediate distinct steps in the adhesion cascade. a 4 b 1 mediates rolling and adhesion strengthening, whereas LFA-1 is needed for firm adhesion and migration.…”
mentioning
confidence: 99%
“…However, integrin function is regulated by changes in phosphorylation and protein interactions in the cytoplasmic domains. [7][8][9][10] LFA-1 and a 4 b 1 mediate distinct steps in the adhesion cascade. a 4 b 1 mediates rolling and adhesion strengthening, whereas LFA-1 is needed for firm adhesion and migration.…”
mentioning
confidence: 99%
“…In this regard, integrins have altered interactions with their microenvironment may give drastic consequences for cell fate as provide cell tend to lose their original adhesion, recognizing a different substrate and reconfigure it with characteristics that enable metastasize [21][22]. It is known that the increase and alteration of integrin expression is indicative of progression of melanoma [23]. Many integrins are found altered in metastatic melanoma (TABLE 1).…”
Section: Melanoma Metastasismentioning
confidence: 99%
“…The importance of integrin ␤ chain phosphorylations in these activation events leading to integrin activation, actin cytoskeleton reorganization, cell adhesion, migration, and phagocytosis is well established, but far less is known about ␣-chain cytoplasmic events involved in integrin activity and functions (3,41). It has previously been shown that in neutrophils, monocytes, and mononuclear cells, CD11c is constitutively phosphorylated and the CD18 becomes phosphorylated upon activation (26,27).…”
Section: S1158a Mutation Of Cd11cmentioning
confidence: 99%
“…Phosphorylation of Thr-758 on the ␤ 2 chain of CD11a/CD18 results in recruitment of 14-3-3 proteins followed by binding of the adaptor protein Tiam1 and activation of the small G protein Rac-1 (3,23,24). These events result in reorganization of the cytoskeleton and increased adhesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation